Inter-industry wage differentials in EU countries: What do cross-country time-varying data add to the picture? - Philip Du Caju; Gábor Kátay; Ana Lamo; Daphne Nicolitsas; Steven Poelhekke (National Bank of Belgium, 2010)
This paper documents the existence of inter-industry wage differentials across a large number of industries for eight EU countries (Belgium, Germany, Greece, Hungary, Ireland, Italy, the Netherlands and Spain) at two different points in time (in general, 1995 and 2002). It then looks into possible explanations for the main patterns observed. The analysis uses the European Structure of Earnings Survey (SES), an internationally-harmonised matched employer-employee dataset, to estimate inter-industry wage differentials conditional on a rich set of employee, employer and job characteristics. After investigating the possibility that unobservable employee characteristics lie behind the conditional wage differentials, a hypothesis which cannot be accepted, the paper considers the role of institutional features, as well as industry structure and performance in explaining inter-industry wage differentials. The results suggest that inter-industry wage differentials are consistent with rent-sharing mechanisms and that rent-sharing is more likely in industries with firm-level collective agreements and with higher collective agreement coverage
Keywords: J31; J41; J51; 330; inter-industry wage differentials; rent sharing; unobserved ability; Sektorale Lohnstruktur; Humankapital; Unternehmenserfolg; Lohnbildung; Erfolgsbeteiligung; EU-Staaten